Risk Assessment of Large Language Model Implementation in the Electric Power Sector of Ukraine - Kravtsov, Hryhoriy; Kravchuk, Oleksandr; Taranowski, Artem; Sinko, Dmytro; Samoylov, Victor (Artificial Intelligence and Applications, 2026)
This study explored the key aspects and risks associated with the implementation of large language models (LLMs) in the electric power sector of Ukraine. We propose a unique taxonomy of risks, along with a hierarchical structure that enables their assessment using the analytic hierarchy process (AHP) developed by T. Saaty. The LLM lifecycle is described with a focus on both human and technological factors (from knowledge selection and training to operational deployment). The study addresses critical concerns related to confabulations, sensitive information leakage, compliance with personal data protection regulations, and the safeguarding of trade secrets. The paper highlights the importance of employing tools for hallucination detection, sentiment analysis, and legal compliance monitoring. A separate section presents an in-depth analysis of LLMs’ readiness to accurately digitize graphical content—such as schematics, diagrams, and technical drawings, which are common for documentation in the energy sector worldwide. A series of experiments using the state-of-the-art generative AI systems revealed significant limitations in interpreting complex diagrams, logical structures, and semantic relationships between elements. The findings demonstrate both the potential and the critical limitations of LLMs in energy-related applications, particularly in processing graphical content, making decisions based on synthetic data, and managing risks associated with model training, operation, and upgrades. Received: 13 August 2025 | Revised: 1 December 2025 | Accepted: 15 January 2026 Conflicts of InterestThe authors declare that they have no conflicts of interest to this work. Data Availability StatementThe data that support the findings of this study are openly available in Github at https://github.com/oleksandrkravchukatpimee/LLM-risks-evaluation/blob/3443a610d9b2f9a9f8db52b280f2f4fb247525c1/AHP.xlsx and https://gist.github.com/taranowskiatpimee/174973d140a84da2b5c3b365a34f949c. Author Contribution StatementHryhoriy Kravtsov: Conceptualization, Methodology, Writing – original draft, Writing – review & editing, Supervision. Oleksandr Kravchuk: Methodology, Validation, Investigation, Writing – original draft, Writing – review & editing. Artem Taranowski: Methodology, Investigation, Resources, Writing – original draft, Writing – review & editing. Dmytro Sinko: Methodology, Investigation, Writing – original draft. Victor Samoylov: Conceptualization, Supervision.
Keywords: electric power sector; large language model (LLM); generative AI; risk assessment; accountability